Electrochemically enabled sustainability : devices, materials, and mechanisms for energy conversion - Chan, Kwong-Yu (Chemical engineer); Li, Chi-Ying Vanessa (CRC Press, 2014)
"With contributions from leading researchers in their fields, this book provides an overview of the most important electrochemical power sources in development today. Focusing on materials, design, and performance, the text presents the most recent and innovative technologies employed in battery and fuel cell technology. Topics include acid/alkaline batteries, microbial fuel cells, Li-Air, Li-Sulphur, flow batteries, lithium ion batteries, lead acid batteries, supercapacitors, photoelectrochemistry, and carbon dioxide electroreduction. The book discusses the advantages of these fuel cells over conventional power sources and their future applications"--